(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to compare perioperative outcomes of patients who underwent hysterectomy and uterine-sparing surgery in patients operated for the abnormally invasive placenta and to compare the results of cesarean section hysterectomy and uterus-sparing surgery which is the standard surgical approach for abnormally invasive placenta cases.Material and Methods: The record of 45 patients who were treated for abnormally invasive placenta in our clinic between January 2011 and May 2019, were reviewed retrospectively. Fifteen of these patients underwent cesarean hysterectomy, while 30 patients underwent conservative surgery. The decision to perform conservative surgery or hysterectomy was made according to the preferences of the patients. Demographic data, amount of bleeding, gynecological and obstetric histories, laboratory parameters, blood transfusions and duration of hospitalization were recorded. Data were obtained using the hospital electronic archive database.Results: The perioperative results of the conservative surgery group were superior to the hysterectomy group. In the perioperative period, all patients in the hysterectomy group received transfusion therapy, while 54.5% of the conservative surgery group received transfusion therapy (p=0.04). The mean amount of bleeding in the hysterectomy group was 2160(495-5715) mL and 1215(180-3645) mL in the conservative surgery group (p =0.04). When the hospitalization periods of both groups were examined, the mean duration of hospitalization was 6 (3-17) days in the hysterectomy group and 3(1-16) days in the conservative surgery group (p = 0.012). Conclusions: Although the standard treatment for placenta invasion anomalies is cesarean hysterectomy, conservative (uterine sparing) surgery seems to be feasible for patients who desire fertility despite surgical difficulties. Therefore, the surgical treatment of placenta invasion anomalies should be individualized.